PV-based hybrid residential microgrid with hydrogen and battery energy storage options: a Northern Italy case study. Issue 1 (1st December 2022) - Damato, A; Iamarino, M.; Ferraro, A; D'Angola, A
Abstract: Residential microgrids based on renewable energy sources (RES) are promising solutions for the ongoing energy transition but, at the same time, must also cope with the intermittency of the energy source and the limited energy storage capacity. To overcome such problems, RES-based microgrids usually rely on backup powering systems, such as a stable connection to the main grid or the presence of emergency electricity generators. In order to significantly increase the autonomy of the microgrid and limit the presence of backup solutions, an additional energy storage system based on hydrogen is proposed here, which complements the more classical option of energy storage in batteries. The microgrid under investigation is composed by a PV system, a lithium-ion battery for short term energy storage, and a hydrogen-based storage system composed of a PEM electrolyzer, a pressurized hydrogen tank and a low temperature PEM fuel cell stack. The system is managed by a control system which balances at each time the energy demand with the energy produced from different sources. Results reflect the role of hydrogen as efficient long-term storage option, while the battery fulfills short-terms storage needs. With properly sized components, the microgrid turns out to be fully autonomous during one year and can therefore work also in off-grid mode. The impact of an improved energy management approach is also highlighted, which may lead to increased hydrogen production and higher level of autonomy of the microgrid.